Developmental factors and drug use in young offenders. Issue 1 (13th March 2017) - Madden, Adele; Ireland, Carol A.
Abstract : Purpose: Young offenders are known to have more chaotic experiences in childhood than non-offenders, and this impacts on their attachments, coping styles and early maladaptive schemas (EMS). The purpose of this paper is to explore the relationship between these factors and drug use. Design/methodology/approach: This study used self-report questionnaires on a sample of 105 incarcerated young offenders. Findings: Attachment styles did not differentiate drug users from non-drug users. Drug users were found to be no more likely than non-drug users to use avoidant coping styles. However, they were more likely to have emotional coping styles. Drug users had more EMS, and overall, those with insecure attachments had more EMS. Individuals with emotional coping styles scored higher than those with rational coping styles on several EMS. Those with emotional coping styles scored lower on the emotional inhibition EMS than those with rational coping styles. Practical implications: The evidence presented has implications for the understanding of drug use in young offenders by: providing support to the model proposed by Young et al. (2003) regarding how insecure attachments can contribute to EMS; providing support for Crittenden's (2008) model of attachment whereby problematic behaviours such as drug use can be a strategy the individual uses to protect themselves at times of threat or discomfort; highlighting the need for an integrated model of substance use in offenders which incorporates early experiences, attachments and EMS; and highlighting why substance use may become a coping strategy in young offenders and how to engage them to meet their needs in pro-social ways. Originality/value: The study contributes to the understanding of attachment, coping and drug use in a young offender population. It sets foundations in the authors' understanding of patterns of EMS in young drug users and highlights the need for an integrated model of substance use which incorporates early experiences, attachments and EMS.